Patient safety for people experiencing advanced dementia in hospital: A video reflexive ethnography. (July 2023) - Dadich, Ann; Rodrigues, Jade; De Bellis, Anita; Hosie, Annmarie; Symonds, Tamsin; Prendergast, Justin; Bevan, Alan; Collier, Aileen
Background: Patient safety for people experiencing dementia in acute hospitals is a global priority. Despite national strategies as well as safety and quality guidelines, how safety practices are enacted within the complexities of everyday work are poorly understood and articulated. Methods: Using video reflexive ethnography, this 18-month study was conducted within an inpatient geriatric evaluation and management unit for people experiencing dementia and/or delirium in Australia. Patients, family members, and staff members participated by: allowing researchers to document fieldwork notes and video-record their practices and/or accounts thereof; and/or interpreting video-recordings with researchers to co-analyse and make sense of the data. Results: Safe care for people experiencing advanced dementia involved: negotiating risk via leadership, teamwork, and transparency; practice-based learning through situated adaptation; managing personhood versus protocols by doing the 'right' thing; joyful and meaningful work; as well as incorporating patient and family voices to do safety together. Conclusion: Patient safety for people experiencing dementia requires continuous responsiveness and prioritising in the context of multiple risks by a staff collective with a shared purpose. Ongoing research to better understand how the nuances of patient safety unfold in everyday complex clinical realities in diverse contexts and with key stakeholders is required.